Epidemiology of Liver Cancer in Europe - F Xavier Bosch; Josepa Ribes (Canadian Journal of Gastroenterology)
Liver cancer (LC) ranks fifth in frequency in the world, with an estimated 437,000 new cases in 1990. The estimates are different when LC frequency is analyzed by sex and geographical areas. In developed areas, the estimates are 53,879 among men and 26,939 among women. In developing areas, the estimates are 262,043 in men and 93,961 in women. Areas of highest rates include Eastern and South Eastern Asia, Japan, Africa and the Pacific Islands (LC age-adjusted incidence rates [AAIRs] ranging from 17.6 to 34.8). Intermediate rates (LC AAIRs from 4.7 to 8.9 among men) are found in Southern, Eastern and Western Europe, Central America, Western Asia and Northern Africa. Low rates are found among men in Northern Europe, America, Canada, South Central Asia, Australia and New Zealand (LC AAIRs range from 2.7 to 3.2). In Europe, an excess of LC incidence among men compared with women is observed, and the age peak of the male excess is around 60 to 70 years of age. Significant variations in LC incidence among different countries have been described and suggest differences in exposure to risk factors. Chronic infection with the hepatitis B virus (HBV) and hepatitis C virus (HCV) in the etiology of LC is well established. In Europe, 28% of LC cases have been attributed to chronic HBV infection and 21% to HCV infection. Other risk factors such as alcohol consumption, cigarette smoking and oral contraceptives may explain the residual variation within countries. Interactions among these risk factors have been postulated. New laboratory techniques and biological markers such as polymerase chain reaction detection of HBV DNA and HCV RNA, as well as specific mutations related to LC, may help to provide quantitative estimates of the risk related to each these factors.